KEBIASAAN MAKANAN DAN FAKTOR KONDISII KAN KURISI, Nemipterus tambuloides Blkr. DI PERAIRAN TELUK LABUAN, BANTEN [Food Habits and Condition Factor of Fiveline Threadfin Bream, Nemipterus tambuloides Blkr. in Labuan Bay, Banten] - Djadja S. Sjafei; Robiyani Robiyani (Jurnal Iktiologi Indonesia, 2001)
The research was conducted in Labuan Bay, Banten from April - June 1999. The fish sample was collected once in every five days. The total fish collected were 483 with 75 - 265 mm of total length and 4.85 - 169.81 grams in weight. Sexual composition was 252 male, 183 female, and 48 of the ambiguous sex. The fish sample was divided into 4 groups of total length (small, medium, and extra large). The medium size was 124 -171 mm) was the most number of the sample (248). According to length weight relationship the growth pattern of the fish was negative allometric. Condition factor of the fish was increased from small to medium size. While the biggest size (extra large) the condition as decreased. This phenomenon maybe because a lot of their gonad were in atresia, A lot of the condition of food material was destructed and impossible to be identified. The female primarily consumed shrimp and squilla. The male feed on shrimp, crab, and fish. According to the time-series of sampling the shrimp had primer index, and the second crab, the third was fish.ABSTRAKPola pertumbuhan ikan kurisi termasuk allometrik negatip. Faktor kondisi kian besar dengan semakin panjang ukuran ikan Ikan kurisi termasuk kedalam kelompok karnivor, dengan makanan utamanya udang. Ikan betina mengkonsumsi terutama udang dan squilla, sedangkan ikan jantan mengkonsumsi udang, kepiting, dan ikan. Tidak ada perubahan jenis maupun IP makanan ikan kurisi berdasarkan waktu. Semakin panjang ukurannya, ikan kurisi semakin mengkonsumsi ikan sebagai makanannya.